UPAYA MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SDN 1 PASAR BANGGI DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SEMESTER I TAHUN PELAJARAN 2018/2019 MELALUI SUPERVISI AKADEMIK TEKNIK KUNJUNGAN KELAS - Wijayanti, Maria Aris (UNIVERSITAS SLAMET RIYADI, 2019)
The purposes of this reasearch are 1) describing the efforts of increasing the elementary school 1 Pasar Banggi teachers pedagogic competence in order to increase the students learning motivation at the first semester of 2018/2019 academic year by class visitation technique of academic supervision and 2) analysing the increase of increasing the elementary school 1 Pasar Banggi teachers pedagogic competence in order to increase the students learning motivation at the first semester of 2018/2019 academic year by class visitation technique of academic supervision. The type of this research is School Action Research (SAR). The action of this research is class visitation. The place of this research is the elementary school 1 Pasar Banggi, Subdistrict of Rembang, Regency of Rembang. The time of this research is the early first semester of 2018/2019 academic year. The subjects of this research are the class teachers (CT) and the subject teachers (ST) in the elementary school 1 Pasar Banggi, Subdistrict of Rembang, Regency of Rembang, consist of six CT and three ST. The technique of collecting data is using nontest technique. The tools of collecting data are using the sheets of observation and documentation. The data of this research is including teachers pedagogic competence in order to increase the students learning motivation. The data of this research are qualitative and quantitative. The technique of analizing data is decriptive comparation. The procedure of this research is using Cycle Model, consist of four steps: planning, action, observation and reflection. The results of this research are 1) the efforts of increasing the elementary school 1 Pasar Banggi teachers pedagogic competence in order to increase the students learning motivation at the first semester of 2018/2019 academic year by class visitation technique of academic supervision are focussing on the coaching, 2) the efforts of increasing the elementary school 1 Pasar Banggi teachers pedagogic competence in order to increase the students learning motivation at the first semester of 2018/2019 academic year by class visitation technique of academic supervision are individually and participative and 3) the elementary school 1 Pasar Banggi teachers pedagogic competence in order to increase the students learning motivation at the first semester of 2018/2019 academic year by class visitation technique of academic supervision increased and included very high (A) category.Â Key words: Pedagogic, Teacher, Learning Motivation, Academic Supervision